Effect of Whey-to-Casein Protein Ratio in Chocolate-Vanilla Milk Beverage on Satiation and Acute Energy Intake - Angela, Amelinda; Antono, Lina; Kurniati, Astri; Pertiwi , Kamalita; Wu , Mardi (Agriculture and Natural Resources, 2015)
The satiating effect of dietary protein could be beneficial to fight obesity by improving weight loss. Whey and casein protein have different digestion rates and combining them may result in a prolonged satiating effect. This study investigated the effect of the whey/casein ratio on subjective appetite ratings and acute energy intake. Twelve healthy men with normal weight received a standardized breakfast followed by one of the three preloads (milk beverage containing 15 g protein with whey to casein protein ratios of 20:80, 50:50, or 80:20) in a randomized, single-blind, cross-over study. Subjective appetite ratings were measured using a visual analog scale while consecutive energy intake was measured through ad libitum lunch and dietary recalls of food and drinks consumed during the remainder of the experimental day. The results showed that there was no significant effect of the whey to casein protein ratio in milk beverages on the appetite ratings and subsequent energy intake. A high protein content, as opposed to the type of protein, may be of greater importance in determining the satiating properties of protein and should be taken into account when developing weight loss products. Further investigation is needed to study the effect of the ratio on metabolic satiety properties and the shelf life of the product.